Relationship of comorbidities and heart failure mortality in the city of São Paulo, Brazil - Koike,Marcia Kiyomi (2016)
OBJECTIVE: The epidemiology of heart failure mortality in the city of São Paulo, Brazil has not been studied. The present study aims to characterize comorbities associated to cardiac heart failure deaths in São Paulo between 2000 and 2012. METHOD: The mortality information system (SIM/DataSUS) was evaluated and the following parameters were retrieved: age, sex, race, level of education and comorbidities (hypertension, diabetes, obesity, chronic obstructive pulmonary disease). Socioeconomic status was estimated by years of schooling, as: lower (0-3 years) and higher (> 3 years). We analyzed 14,814 death certificates. RESULTS: There was a prevalence of subjects in the subgroup: female, white, married or divorced, aged 78 years and lower socioeconomic status. Hypertension and diabetes were the most frequent comorbidities. There were associations of (a) diabetes with age, (b) age, gender and educational level with hypertension in individuals belonging to both the lower and higher socioeconomic levels. CONCLUSION: Individuals who died of congestive heart failure in São Paulo are mostly elderly, women, caucasian, with little education. Hypertension and diabetes are the two most common chronic diseases associated with death bycongestive heart failure.